View at the history of understanding miracle of Kuran - Gafarov, Aliraza (Eurasian Journal of Religious Studies, 2016)
The article examines the history of translation of the holy Kur’an into Azerbaijani language. Here is shown that the holy Kur’an had sent by Allah not only for a definite period, but It had sent for all humanity till the Last Day. In the article also noted the great role of the eminent, faithful people who tried to translate the holy Kur’an though some of them insisted that it is impossible to give the exact translation of the holy Kur’an. Here also estimated the role of Sheykhulislam Allahshukur Pashazadeh who was the first national historic on islamism and the author of the tremendous articles and works on islam culture, the history of islam thought, the history of shiism in Islam and the history of interpretation and translation of the holy Kur’an. The author shows that as result of manifestation of immense love to the Koran and immense need for it, transfer and commenting of this Sacred Book proceeds and it is represented to the people as invaluable gift. The sacred Book, a perfection treasury – the Koran is a miracle, the inexhaustible treasury granted for each representative of mankind, and at all times, attracting each believer with the eloquence and a charm, eyelids will keep all Islamic world in the magic charms.